Proceedings of the 22nd International Conference on Engineering and Product Design Education 2020
DOI: 10.35199/epde.2020.3
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Responsible Design with the Product Impact Tool

Abstract: Industrial Design Engineers have a social responsibility by the very nature of their activities, bringing new products and services into the world of the user. Within the design related research chairs of our university we strive to shape this responsibility in the context of the design of Human Technology Relations. This paper will report on the experiences with teaching responsible design in the context of an Industrial Design Engineering Master's course "Create the Future". In this course student groups exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Traditional examples of SIA include surveys and questionnaires, workshops, community meetings, studies, advisory committees, and checklists. Conversely, digital examples of SIA applicable during the R&D phase include online tools such as the Product Impact Tool (https:// productimpacttool.org/) which guides the impact assessment of commercial and non-commercial products [100], the Constructive Technology Assessment (CTA; https://cta-toolbox.nl/) toolbox that lists different tools for technological assessment [101], and the Responsible Research and Innovation (RRI; https://rri-tools.eu/) toolkit, which assists researchers in selecting the most fit-forpurpose RRI tool to implement [102].…”
Section: Social Impact Assessment and Mitigation Of Negative Social I...mentioning
confidence: 99%
“…Traditional examples of SIA include surveys and questionnaires, workshops, community meetings, studies, advisory committees, and checklists. Conversely, digital examples of SIA applicable during the R&D phase include online tools such as the Product Impact Tool (https:// productimpacttool.org/) which guides the impact assessment of commercial and non-commercial products [100], the Constructive Technology Assessment (CTA; https://cta-toolbox.nl/) toolbox that lists different tools for technological assessment [101], and the Responsible Research and Innovation (RRI; https://rri-tools.eu/) toolkit, which assists researchers in selecting the most fit-forpurpose RRI tool to implement [102].…”
Section: Social Impact Assessment and Mitigation Of Negative Social I...mentioning
confidence: 99%
“…This tool is intended to be useful for analysing the effects of technologies, and to help to design for desired impact on society. We have used and tested this tool in industrial design education extensively, especially in the context of responsible design [15][16][17]. Within the Tech-Wise project we found that it also stimulates ethical deliberation about technologies [18,19].…”
Section: Ethical Deliberationsmentioning
confidence: 99%
“…This course is part of the Master in Industrial Design Engineering of the University of Twente. The course is especially targeted at developing novel designs for innovative technologies (Eggink and Reinders 2013). In previous years this approach was also applied to Concentrating PV and other PV technologies (Reinders 2008;Reinders et al 2009Reinders et al , 2013.…”
Section: Ut's Project Description (2016)mentioning
confidence: 99%